CANNED GARLICKY TOMATO (TECHNICAL SPECIFICATIONS) - L. V. Pavlov; I. Yu. Kondratieva; T. A. Sannikova; V. A. Machulkina (Овощи России)
The aim of technical specifications is the development of quality rating system of canned garlicky tomato in vinegar and tomato sauces with garlic, sugar, salt, and vinegar. The project of the technical specifications is developed for the first time inRussia.